Hacia un enfoque de conservación basado en entrelazamientos de Naturaleza y Cultura. Una mirada desde Japón en el contexto del Patrimonio Mundial - Ishizawa Escudero, Maya Natalia (2020)
The Convention for the Protection of the World Cultural and Natural Heritage adopted by UNESCO in 1972 is characterized for being the only international legal instrument that considers both the conservation of natural and cultural sites with Outstanding Universal Value. Yet, in its implementation, the system has been divided in two sectors: one dedicated to the conservation of nature, and other dedicated to the conservation of cultural heritage. The objective of this article is to explain the particularities of the Japanese conservation system and its conceptual contributions in the international context, which have allowed the development of an experimental capacity building programme organized by the UNESCO Chair on Nature-Culture Linkages in Heritage Conservation at the University of Tsukuba in Japan. In these workshops, capacity building has been explored from the nature-culture perspective in the region of Asia and the Pacific.